Shell model calculations in the A=90-98 mass region. A study of the N=51. nuclei - Divari, P.; Skouras, L. D. (HNPS Advances in Nuclear Physics, 2020)
The properties of nuclei with 39 < Ζ < 47 and N=51 are investigated in large scale shell-model calculations. The doubly closed nucleus 100Sn is selected as the reference state and the nuclei under examination are described in terms of proton holes and a single neutron outside the inert core. The proton holes are distributed in a model space consisting of the orbitals g9/2, p1/2, p3/2 while f5/2 is sometimes also considerd. Similary the model space for the single neutron includes the orbitals g7/2, d5/2, d3/2, s1/2 and in certain cases h11/2. The effective two-body interaction and the matrix elements of the effective operators were determined by introducing second-order correctios to the Sussex matrix elements. The single proton holes as well as the single-neutron energies were treated as parameters which were determined by least-squares fit to the observed levels of 39 < Ζ < 47, N=50 and Ν=51 respectively. The results of the calculation were found to be in satisfactory agreement with experimental data and this enable us to make predictions about the properties of some exotic nuclei in the vicinity of 100Sn.